辛亥革命时期前后黄兴与孙中山的立国思想 - 黄, 昕 (2023)
孙中山与黄兴二人的立国思想离不开民族主义，可以说两人的立国思想就是通过民族主义的进化发展而来的。本篇论文探讨辛亥革命前后孙中山与黄兴的立国思想之演变，尝试分析孙中山与黄兴两人思想之差异。孙中山与黄兴的初期立国思想的萌发都是受外海环境影响。孙中山的思想萌发始于夏威夷檀香山留学期间，黄兴的思想萌发始于日本留学期间，亲眼见证了日本明治维新后繁荣的景象。两人结识后，双方在立国的思想上就取得高度的共识，并一起走向革命建国之路，两人在革命过程中不断完善其思想架构，对于革命的主要讨伐对象做出更多新的思考。 辛亥革命后，中国进入新阶段，孙黄二人也将思想重心从革命运动中转移到如何建国上，在制定政策上，孙中山与黄兴因政见不同产生了第一次较为严重的分歧，最终以黄兴做出让步，孙中山的思想主张得以落实。民国建国初期，袁世凯利用宪法的漏洞，篡夺革命果实。孙中山黄兴等人被迫进行二次革命，在后来对于二次革命的理解上，孙中山与黄兴二人又一次产生意见上的分歧，致使黄兴离开同盟会，孙中山与黄兴二人合作至此结束，黄兴抱憾而终时。孙中山对他的死去作沉痛的哀悼，两人生前所留下的思想财富，对中国整个社会的进步产生深远影响，让民主共和的政治理念深入人心。 回溯两人生前成就，当两人的意见产出分歧时，最后做出让步的总是黄兴，可见黄兴对中国革命事业的奉献精神，其任劳任怨，大度谦和的精神值得我们后辈学习。而孙中山作为辛亥革命事件中最主要的领导人，其三民主义思想对当时乃至后世社会的发展都有所影响，与此同时，黄兴一辈子虽短却甚有意义，他留下的精神财富，特别是在辛亥革命全过程中立下的丰功伟绩，是非常宝贵的，因此,人们把黄兴和孙中山同列为中华民国的开国元勋。The nation building ideas of Sun Yat-sen and Huang Xing are inseparable fromnationalism, the ideas are developed through the evolution of nationalism. This dissertation explores the evolution of Sun Yat-sen and Huang Xing's nation buildingideas before and after the Xinhai Revolution, and analyze the differences betweentheideas of Sun Yat-sen and Huang Xing. The germination of Sun Yat-sen's and Huang Xing's early ideas was influencedby their living experiences in overseas. Sun Yat-sen's ideas germinated duringhis study in Honolulu, Hawaii, while Huang Xing's ideas germinated during his studyinJapan, when he witnessed the prosperity of Japan after the Meiji Restoration. After thetwo became acquainted, they share a commonality in the nation building idea, together they adapt a revolutionary method in building a new nation. In the courseof the revolution, both of them have constantly improved theirs ideological structureand generated more new thinking about the main opponent of the revolution. After the Xinhai Revolution, China entered a new stage, Sun Yat-sen and HuangXing has also shifted their ideological focus from the revolutionary movement tomethods of nation building. On the implementation of the nation building policies, Sun Yat-sen and Huang Xing had the first serious differences due to different political views, after Huang Xing made his concessions, Sun Yat-sen's ideological ideas wereimplemented. Later during the second revolution period, Sun Yat-sen and Huang Xing once again had differences of opinion, which resulting in Huang Xing leavingtheLeague, and the cooperation between Sun Yat-sen and Huang Xin came to an end. When Huang Xing passed away, Sun Yat-sen has mourned him with great sadness. The intellectual wealth left by the two men had a profound impact on the progress of the modern Chinese society, and the new political concept of democracy andrepublicanism was deeply rooted in the hearts of the people. Looking back to the achievements of the two people, when the opinions of thetwo people were different, it was always Huang Xing who made concessions intheend, which shows Huang Xing's dedication to the struggle of the Chinese revolution, his spirit of hard work and his generous and humble spirit has made an example of learning for our descendants. As the most important leader of the Xinhai Revolution, Sun Yat-sen's ideas of the Three People's Principles had made an impact onthedevelopment of society at that time and even in later generations, Although HuangXing’s life was short, the spiritual wealth he left behind was also very precious, especially his great achievements made in the whole process of the Xinhai Revolution. therefore, people consider Sun Yat-sen and Huang Xing as the founding fathers of theRepublic of China